Analysis of Pencat Silat Athlete Speed in Pekalongan City - M. Riski Adi Wijaya; Setya Rahayu; Mahalul Azam; Sri Sumartiningsih (Universitas Negeri Semarang, 2023)
This research aims to analyze the speed component of Pencak Silat athletes in Pekalongan City. The research method used was descriptive with data collected through a 30m sprint speed test. The research subjects were five Pencak Silat athletes who will participate in PORPROV Jawa Tengah 2023. The results showed that 80% of the Pencak Silat athletes in Pekalongan City had poor speed conditions and 20% had less than optimal speed conditions. Analysis of the speed component showed that athlete speed is influenced by factors such as muscle strength, running technique, and mental strength. Additionally, the research revealed a significant difference in speed between male and female athletes in Pekalongan City, with female athletes demonstrating lower speed compared to male athletes. Although height, weight, and age did not significantly influence the speed of Pencak Silat athletes in Pekalongan City, factors such as muscle strength, running technique, and mental strength can influence athlete speed. In conclusion, this research highlights that the speed of Pencak Silat athletes in Pekalongan City is affected by various factors, and coaches and Pencak Silat athletes can use this study as a reference when developing speed training programs.